تأثير الكثافة النباتية والتسميد الأزوتي على بعض الصفات الكيميائية والفيزيولوجية والانتاجية للذرة الرفيعة Sorghum bicolor L. (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The research was carried out in the coastal area at Governances Latakia  ( Bauqa Farm), and in the laboratories of the Faculty of Agriculture, Tishreen University  during the season 2018 in order to study the effect of plant density and nitrogen fertilization and their interaction on some chemical, physiological and productivity parameters of sorghum plant to obtain the highest grain yield. The design of the experiment was Randomized Completely  Block Design (RCBD) with the arrangement of split plot design with three replicates. The density treatments were distributed in the main plots (3.33 - 5-10 plants / m2), while nitrogen fertilization levels were allocated in the sub plots ( 200 - 300 – 400 leg/ha) in addition to the control treatment without nitrogen addition. Jumbo variety  was used which obtained from  General Orgnization of Seed Multiplication in Latakia. The density of 10 plants / m2 and the  nitrogen fertilization of 300 kg / ha  gave the highest  grain yield (1.64 ton / ha), under the conditions of the experiment. While the density of 3.33 plants / m 2 and the  nitrogen addition of n 400 kg / ha  gave the     highest plant height(155.00), and the number of leaves(19.33), and the weight of 100 grains(3.92), and chlorine elephant total(817.46), and the proportion of fat(21.61%). Cereal productivity was negative significantly correlated with moisture percentage (r= 0.430 **),ash (r = 0.583) and fiber(r = 0.459 * *) This indicates the lack of correlation between the increase in yeild  productivity with improvement qualty . نفذ البحث في في المنطقة الساحلية محافظة اللاذقية (مزرعة بوقا)، وفي مخابر كلية الزراعة ،بجامعة تشرين للموسم الزراعي 2018، بهدف دراسة تأثير الكثافة النباتية والتسميد الأزوتي والتفاعل بينهما في بعض المؤشرات الكيميائية والفيزيولوجية والانتاجية لنبات الذرة الرفيعة للحصول على أعلى أنتاجية  والنوعية من الحبوب في وحدة المساحة. نفذت التجربة وفق تصميم القطاعات العشوائية الكاملة (RCBD) بترتيب القطع المنشقة (Split plot design)  لمرة واحدة وبثلاثة مكررات، حيث وزعت معاملات الكثافات على القطع الرئيسية (3.33 – 5 – 10 نبات/م2)،  بينما تضمنت القطع الثانوية معدلات التسميد (100 – 200 – 300 - 400 كغ/هـ) بالإضافة لمعاملة 0 بدون سماد أزوتي.استخدم صنف (جامبو) الذي تم الحصول عليه من مؤسسة اكثار البذار في اللاذقية. أعطت الكثافة  10نبات/م2 ومستوى  التسميد 300 كغ/هـ  والتداخل بينهما أعلى انتاجية من الحبوب(1.64 طن/ه) ضمن ظروف منطقة البحث. بينما تفوقت الكثافة 3.33 نبات/م2 ومستوى  التسميد 400 كغ/هـ  في الصفات أهمها ارتفاع النبات(155.00سم)، وعدد الأوراق(19.33ورقة)، ووزن 100 حبة(3.92 غ)،والكلوروفيل الكلي(817.46)، ونسبة الدهن في النبات(21.61%). ارتبطت انتاجية الحبوب طن/هـ بشكل معنوي سلبي مع نسبة الرطوبة (r=-0.430**)،الرماد (r=-0.583**) والألياف (r=-0.459**) وهذا يشير لعدم الارتباط بين زيادة الغلة وتحسين الصفات النوعية سابقة الذكر.